Sediment Depth-Dependent Spatial Variations of Bacterial Communities in Mud Deposits of the Eastern China Marginal Seas - Qiao, Yanlu; Liu, Jiwen; Zhao, Meixun; Zhang, Xiao-Hua (Frontiers in Microbiology, 2018)
The mud sediments of the eastern China marginal seas (ECMS) are deposited under different hydrodynamic conditions with different organic matter sources. These events have been demonstrated to exert significant influences on microbial communities and biogeochemical processes in surface sediments. However, the extent to which such effects occur in subsurface microbial communities remains unclear. In this study, both horizontal and vertical (five sites, each for eight layers) distributions of bacterial abundance and community composition in mud deposits of the South Yellow Sea (SYS) and East China Sea (ECS) were investigated by quantitative PCR and Illumina sequencing of the 16S rRNA gene. Both bacterial abundance and diversity were higher in the ECS than in the SYS, and tended to be higher in up than in deep layers. Proteobacteria (JTB255 marine benthic group), Acidobacteria and Bacteroidetes were dominant in the upper layers, whereas Lactococcus, Pseudomonas and Dehalococcoidia were enriched in the deep layers. The bacterial communities in surface and subsurface sediments showed different inter-taxa relationships, indicating contrasting co-occurrence patterns. The bacterial communities in the upper layer samples clustered in accordance with mud zones, whereas those in the deep layer samples of all sites tended to cluster together. TOC δ13C and TON δ15N significantly affected the bacterial community composition, suggesting that the abundance and composition of organic matter played critical roles in shaping of sedimentary bacterial communities. This study provides novel insights into the distribution of subsurface bacterial communities in mud deposits of the ECMS, and provides clues for understanding the biogeochemical cycles in this area.